Comparative Investigations on Platinum Cluster Salts. Issue 3 (1st July 2014) - Bignami*, Giulia P. M.; Ceriotti, Alessandro; Mussini, Patrizia R.; Oliva, Cesare; Longoni, Giuliano; Zacchini, Stefano; Gaboardi, Mattia; Mazzani, Marcello; Riccò, Mauro
To evaluate future applications of metallic clusters in nanoscience and nanotechnology, the electronic properties of the high-nuclearity carbonyl anionic platinum cluster [Pt19(CO)22]4‐ were investigated using two different organic cations. In particular, N, N-diethyl viologen dication (Vio2+) and N, N-dimethyl-9, 9-bis-acridinium dication (Acr2+) were employed as counterions, oxidising agents and characterisation probes. The reactions of [Pt19(CO)22]4‐ tetra-n-butylammonium salt, (TBA+)4([Pt19(CO)22]4‐), with both (Vio2+) and (Acr2+), used as tetraphenylborate salts, yielded two new compounds, which were isolated. The stoichiometries and properties of these new compounds were determined and compared on the basis of infrared (IR) solution spectra, electron spin resonance (ESR) analyses, fluorometric spectra, superconducting quantum interference device (SQUID) magnetometry and resistivity measurements. For Vio2+, a cation-exchange reaction produced the final compound (Vio2+)2([Pt19(CO)22]4‐), 'PtVio', which was structurally characterised by single crystal X-ray diffraction (XRD) analysis. However, when using Acr2+, a spontaneous redox reaction occurred and a (Acr+)(TBA+)2([Pt19(CO)22]3‐) stoichiometry for the precipitated solid, 'PtAcr', was inferred from the experimental evidence, leading to an interesting 'doubly-radicalic salt'. This new type of salt, consisting of a radical anionic Pt cluster and a radical cation, is characterised by extremely simple synthesis and isolation processes and by the lowest solid-state resistivity found in high-nuclearity cluster salts with redox-active cations (1).